(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The choice of bee breeds in beekeeping depends on the purpose for which the bee colony will be used. If a bee colony is to be acquired for the purpose of producing commercial honey, it is advisable to select bee breeds that produce a lot of honey.